A good person [videorecording (Blu-Ray)] - Braff, Zach, 1975-; Pugh, Florence, 1996-; Shannon, Molly, 1964-; Uche, Chinaza, 1987-; O'Connor, Celeste, 1998-; Lister-Jones, Zoe; Freeman, Morgan; Fiore, Mauro; Dessner, Bryce (Warner Bros. Entertainment Inc., 2023)
Allison's life falls apart following her involvement in a fatal accident that took the life of Daniel's daughter. As grief-stricken Daniel navigates raising his teen aged grandaughter and Allison seeks redemption, the two discover that friendship, hope, and forgivenessflourishouish in unlikely places.